CRYSTAL STRUCTURE AND MOLECULAR DOCKING ANALYSIS OF DIFURFURYLIDENE SUCCINIC ACID WITH CYCLOOXYGENASES - PRASHANTHA KARUNAKAR,; V. KRISHNAMURTHY,; C. R. GIRIJA,; V. KRISHNA, (International Journal of Pharma and Bio Sciences, 2013)
The structure of 2,3-Bis-(1-furan-2-yl-ethylidene)-succinic acid (Furan succinic acid (FSA)) has been established by X-ray crystallography to understand the structure-activity relationship, which is of paramount importance in the pharmaceutical studies of the compound. Compound showed carbonyl–π and C—H…O interactions along with O-H…O interactions in the assembly of the supramolecular architecture. Crystal structure analysis of FSA possessing anti-inflammatory activity was extrapolated to docking study to elucidate the action against enzyme cyclooxygenases. Using AutoDock suite, FSA was docked at the binding sites of COX-1 and COX-2 enzymes and a strong affinity of -6.55kcal/mol, Ki = 15.93 µM and -6.96kcal/mol, Ki = 7.91µM, respectively was observed with formation of hydrogen bonds and hydrophobic interactions. These results suggest that FSA can be a promising lead for the development of COX family inhibitors.